1998
DOI: 10.1148/radiology.209.3.9844657
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on cerebral blood flow: measurement with ungated two-dimensional phase-contrast MR angiography in 250 adults.

Abstract: Ungated two-dimensional phase-contrast MR angiography is a useful, noninvasive technique for assessing total CBF. By using this technique, a significant decrease in total CBF with age was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
141
4
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(200 citation statements)
references
References 0 publications
40
141
4
4
Order By: Relevance
“…Importantly, the current data are consistent with others that have reported agerelated differences in MCA V mean (Buijs et al 1998;Ainslie et al 2008), and the progressive decline in CBF from the age of 30 to 70 years has been confirmed repeatedly using a variety of imaging techniques (Kashimada et al 1994(Kashimada et al , 1995Buijs et al 1998;Scheel et al 2000;Beason-Held et al 2007;Stoquart-ElSankari et al 2007). …”
Section: Methodological Considerationssupporting
confidence: 91%
See 3 more Smart Citations
“…Importantly, the current data are consistent with others that have reported agerelated differences in MCA V mean (Buijs et al 1998;Ainslie et al 2008), and the progressive decline in CBF from the age of 30 to 70 years has been confirmed repeatedly using a variety of imaging techniques (Kashimada et al 1994(Kashimada et al , 1995Buijs et al 1998;Scheel et al 2000;Beason-Held et al 2007;Stoquart-ElSankari et al 2007). …”
Section: Methodological Considerationssupporting
confidence: 91%
“…CBF during mild-to-moderate intensity exercise: influence of age Despite no disturbances to total cerebral oxygen consumption with healthy aging, there is a progressive decline in CBF (approximately 28-50%) from 30 to 70 years of age (Yam et al 2005;Ainslie et al 2008;Fisher et al 2008;Ogoh and Ainslie 2009) that is associated with global cerebral atrophy Buijs et al 1998). In contrast to healthy YA, as mentioned, only two studies (Fisher et al 2008;Heckmann et al 2003) have examined CBF in middle-aged OA during mild-to-moderate exercise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are consistent with previous findings of age-related decline in brain perfusion measured with positron emission tomography or phase-contrast MRA. 5,22 Engagement in physical activity or aerobic exercise training may ameliorate age-related reduction in brain perfusion. 21,23 A recent study showed that CBFV was elevated in the physically fit individuals over a lifespan from 18-79 years.…”
Section: Effects Of Age and Exercise On Basal Cerebral Blood Flowmentioning
confidence: 99%